2017
DOI: 10.1002/etep.2490
|View full text |Cite
|
Sign up to set email alerts
|

Voltage behaviour in radial distribution systems under the uncertainties of photovoltaic systems and electric vehicle charging loads

Abstract: Summary This paper presents a probabilistic method that accurately verifies the fulfilment of voltage constraints in radial distribution systems (RDSs) with photovoltaic (PV) systems and electric vehicle (EV) charging loads. This problem has not been comprehensively discussed. The proposed probabilistic method (PPM) involves the calculation of input variable cumulants, the linearization of load‐flow equations, and the application of the cumulant method and the Cornish‐Fisher expansion. Obviously, it is first n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 64 publications
(245 reference statements)
0
30
0
Order By: Relevance
“…There are other type studies, e.g., hosting capacity [31], where realistic operation schemes is addressed using Monte Carlo simulations with stochastic EV demands [32][33][34][35][36]. Thus, this work does not intend to replicate the probabilistic behavior of EV connection in a given period.…”
Section: Case Studymentioning
confidence: 99%
“…There are other type studies, e.g., hosting capacity [31], where realistic operation schemes is addressed using Monte Carlo simulations with stochastic EV demands [32][33][34][35][36]. Thus, this work does not intend to replicate the probabilistic behavior of EV connection in a given period.…”
Section: Case Studymentioning
confidence: 99%
“…In some cases, this rise violates respective regulatory limits, causing problems to utilities and customers alike . Comprehensive studies of the technical impacts of PV generators in distribution systems can be found in previous studies …”
Section: Introductionmentioning
confidence: 99%
“…11 Comprehensive studies of the technical impacts of PV generators in distribution systems can be found in previous studies. [12][13][14] In fact, voltage rise is one of the most restrictive technical impacts resulting from the large-scale connection of distributed generators to electric power distribution systems. 11 Therefore, repetitive power flow calculations can be used for connection assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of electric vehicle on voltage profile under different situation is also studied in the literature. () Other impacts such as voltage profile, energy losses, transformer aging, and power quality are also studied in previous studies. ()…”
Section: Introductionmentioning
confidence: 99%
“…The effect of electric vehicle on voltage profile under different situation is also studied in the literature. [9][10][11][12][13] Other impacts such as voltage profile, energy losses, transformer aging, and power quality are also studied in previous studies. [14][15][16] There are few studies on the effect of electric vehicles in the presence of Distributed Generation (DG).…”
mentioning
confidence: 99%